Cardiac catheterization: consequences for the endothelium and potential for nanomedicine. (27th November 2014) - Sobolewski, Peter; El Fray, Miroslawa
Abstract : Cardiac catheterization results in interactions between the catheter and surfaces and the artery lumen, which is lined by the endothelium. These interactions can range from minor rubbing to severe mechanical injury. Further, in the case of radial access, even atraumatic interactions have consequences ranging from clinical complications, such as radial spasm and radial occlusion, to lasting endothelial cell dysfunction. These consequences may be underappreciated; however, endothelial cells play a central role in maintaining vascular homeostasis via nitric oxide production. Existing treatment paradigms do not address endothelial dysfunction or damage and, thus, novel therapeutic approaches are needed. Nanomedicine, in particular, offers great potential in the form of targeted drug delivery, via functionalized coatings or nanocarriers, aimed at increased nitric oxide bioavailability or reduced inflammation. WIREs Nanomed Nanobiotechnol 2015, 7:458–473. doi: 10.1002/wnan.1316 This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Cardiovascular Disease Implantable Materials and Surgical Technologies > Nanotechnology in Tissue Repair and Replacement